Building prosilience for the years ahead: main insights from the Covid-19 pandemic for the way ahead - Amann, Wolfgang (Organizational corruption, crime and COVID-19, 2025)
This chapter provides a summary of challenges regulators, chief compliance officers, faculty members and other stakeholders face when dealing with contemporary corruption. Four factors drive complexity when trying to understand corruption and design anticorruption initiatives. Beyond comprehension, expectations are clear. We ought to arrive at prosilience – a more proactive stance towards building robust systems to bounce back and do so faster than ever before. We link the discussion to strengths-based leadership. All involved personalities and individuals have unique strengths. They can be heavily utilized when fighting corruption – and they also need to be complemented in effective teams in order to avoid blind spots. Finally, there is a clarification that further and creative corruption initiatives are to be expected. Learning faster than the corrupt entities and individual emerges as one key way forward.